Padrão histo-anatômico, degradabilidade e compostos secundários em acessos de maniçoba - Silva, Kleitiane Balduino da (2016)
Anatomical characteristics knowledge, ruminal degradability and forage plants secondary metabolites help to clarify differences in digestibility, especially in species from extreme weather environments, as is the case of Caatinga plants, which may contain structures and different chemicals compounds which limit their digestibility, thus restricting their nutritional value. This study objective was to characterize the anatomical pattern, degradability and determine the secondary compounds in three maniçoba access at different sheet maturation stages (young, mature and senescent). The plant material was collected from three maniçoba access (Manihot spp.), Barra de Santa Rosa city, Boa Vista city and Monteiro city,from the Federal University of Paraiba - Campus II, Active Germplasm Bank (BAG).The data collect was conducted from May 2014 to April 2015, which were selected from each access three plants, which were harvested leaves and petioles for histo-anatomical characterization and degradability by making permanent histological slides. After preparing the same, we proceeded to the evaluation and tissue quantification. Their total area available by the tissue and the epidermis ratio (%) (EPI), sclerenchyma (ESC), xylem more associated fibers (XYL) phloem (FLO), mesophyll (MES) and, when present, chollenchyma. The degradability was given by the difference between the fabric proportion before and after 48 hours ruminal incubation. Through phytochemical screening was identified secondary metabolites present in maniçoba access. It was found that the three access leaf blades had similar proportions to the anatomical features. On petioles occurred proportion variations from access and maturation stages. The stage senescent showed higher proportions for some of their tissues both in leaf blades and petioles. Accesses 02 e 04, because they have higher xylem ratios, decreasing their digestibility. Based on the results, the physiological maturation progress of maniçoba access tissue in the leaves and petioles, provides degradability reduction. Based on the results, the physiological maturation progress of maniçoba access tissue in the leaves and petioles, provides degradability reduction. The 38 th access had a higher digestibility due to a higher mesophyll proportion. The secondary metabolites presence and concentration is variable between accessions and maturation stages.